DIRECTIONS OF DEVELOPMENT OF THE INTERNET OF THINGS IN COMPLEX DEVICE MANAGEMENT SYSTEMS - YAREMKO, Svitlana; KUZMINA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article discusses the concept of the introduction and development of the Internet of Things in the management of complex devices; considers the principles of the IoT management system; highlights the features, advantages and disadvantages of the Internet of Things; contains an analytical overview of the most common industries of use of IoT devices. The article analyzes the stages of the introduction of the Internet of Things for business and elaborates how it will affect the work of the enterprise. Analyzing the scientific literature devoted to this topic, it was found that many researchers were engaged in this issue. The main functions are discussed in detail in the article. that IoT devices must perform. Factors that can harm the development of the Internet of Things have been identified. The main requirements for the implementation of the Internet of Things in any activity where they can be used were analyzed. Forecasts on the development of the Internet of Things from well-known companies and the conclusions they reached in this matter were presented. In general, it can be noted that the use of Internet of Things devices is quite relevant in our time and, despite certain shortcomings, is a modern solution for automating the work process, or simply simplifying the daily life of a person, and is also a tool for increasing business competitiveness Key words: ІоТ, Internet-of-Things, management systems, implementation stages.